Caspase Sensors Based on NanoLuc - Li, Jie; Wang, Jin-lan; Gan, Chun-Yang; Cai, Xue-fei; Wang, Yu-wei; Long, Quan-xin; Sun, Yu-xue; Wei, Xia-fei; Cui, Jing; Huang, Ai-Long; Hu, Jie-Li (Journal of biotechnology, 2022)
Caspases are a family of evolutionary conserved cysteine proteases that play key roles in programmed cell death and inflammation. Among the methods for the detection of caspase activity, biosensors based on luciferases have advantages in genetical encoding and convenience in assay. In this study, we constructed a new set of caspase biosensors based on NanoLuc luciferase. This kind of sensors, named NanoLock, work in dark-to-bright model, with the help of a NanoLuc quencher peptide (HiBiT-R/D) mutated from HiBiT. Optimized NanoLock responded to proteases with high signal to noise ratio (S/N), 1233-fold activation by tobacco etch virus protease in HEK293 cells and > 500-fold induction to caspase 3 in vitro. We constructed NanoLocks for the detection of caspase 1, 3, 6, 7, 8, 9, and 10, and assays in HEK293 cells demonstrated that these sensors performed better than commercial kits in the aspect of S/N and convenience. We further established a cell line stably expressing NanoLock-casp 6 and provided a proof-of-concept for the usage of this cell line in the high throughput screening of caspase 6 modulator. [Display omitted] •New biosensors named NanoLock were developed；•Optimized NanoLock responded to proteases with high signal to noise ratio；•A cell-based assay was established for screening compound modulating caspase 6 activity.